Why Research on Women Entrepreneurs Needs New Directions - Ahl, Helene (Entrepreneurship Theory and Practice, 2006)
Research articles on women's entrepreneurship reveal, in spite of intentions to the contrary and in spite of inconclusive research results, a tendency to recreate the idea of women as being secondary to men and of women's businesses being of less significance or, at best, as being a complement. Based on a discourse analysis, this article discusses what research practices cause these results. It suggests new research directions that do not reproduce women's subordination but capture more and richer aspects of women's entrepreneurship.